Analysis of factors causing stunting in Toddlers - Meilani, Nima; Dahmar, Dahmar; Darmawan, Agus; Amiruddin, Eky Endriana; Ira, Wa (Community Research of Epidemiology (CORE), 2021)
Stunting is a nutritional problem that is often found in children aged 12-36 months. This study aims to determine the determinants of stunting in toddlers which include family income, exclusive breastfeeding, and parenting. The type of research used is quantitative with an observational analytic approach and a cross sectional study design. The total population is 1,280 children under five, a sample of 76 respondents taken by proportional random sampling technique to represent 10 villages. The statistical test used was the Chi square test with a 95% confidence level. The results showed that there was a relationship between family income (p value = 0.001), exclusive breastfeeding (p value 0.006), and parenting style (p value = 0.013) with the incidence of stunting in toddlers. The conclusion of this study shows that family income, exclusive breastfeeding and parenting are related to the incidence of stunting. So it is suggested to mothers to make more use of existing health services and pay attention to the nutritional intake of toddlers and exclusively breastfeed until the age of 6 months.